Marqueurs territoriaux ou marqueurs patrimoniaux : l’appropriation de l’espace marin coutumier au sahel tunisien face aux disruptions des récentes logiques environnementales de l’État - Racha Sallemi (VertigO)
The concept of Traditional Ecological Knowledge (TEK) advocated in international forums on sustainable development seems to emerge as the dominant contemporary paradigm of the protection of biodiversity. Its integration in the creation and management of marine protected areas (MPAs) can constitute a mean to achieve integrated management targets. Building on the experience of the first MPA project in Tunisian sahel in the Kuriat islands (east-central coast), this article analyses the levels of acceptability of the MPA by gauging the level of anchoring of fishermen in the marine space, notably through their TEK. This local body of knowledge encompasses marine environment, biology of marine fauna/flora, and fishing techniques. This knowledge and its use constantly evolve, balancing ruptures and continuity, largely as the result of power relationships among fishermen. In turn, the hierarchy of power among fishermen is shaped by the evolution of fishing techniques and the control over marine space. Over time, a powerful elite has emerged, whose claims about access to marine resources take place outside of the institutional framework and threaten the development of the MPA. The institutional framework itself suffers from a lack of participatory approaches and predominantly authoritarian practices of state authorities. Furthermore, the changes brought about by the 2011 revolution fell short of democratic aspirations, and do not seem to have affected local socio-political dynamics.